2006
DOI: 10.1177/15257401060280010601
|View full text |Cite
|
Sign up to set email alerts
|

Language Maintenance and Loss in Preschool-Age Children of Mexican Immigrants

Abstract: In this study, the authors plotted the Spanish language usage of 10 preschool-age children over the course of 3 years and assigned them to one of two groups: language maintenance and language loss. The authors then compared the groups' scores on structured tasks, language behaviors, and language usage/exposure variables. They found that children in the language loss group presented with more grammatical errors, whereas the language maintenance group performed better on Spanish vocabulary and language tasks. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…The literature on language development of bilingual children has consistently shown that one of the most important languageexternal factors predicting bilingual language acquisition is the amount of exposure (Gathercole and Thomas, 2005;Guiberson et al, 2006;Armon-Lotem et al, 2011;Blom and Vasić, 2011;Chondrogianni and Marinis, 2011;Paradis, 2011;Anderson, 2012;Unsworth, 2013Unsworth, , 2015Paradis and Jia, 2016, among many others). In a setting with one dominant societal language and a minority language, a child's input is typically divided between the two languages and comes from two main sources: home and school.…”
Section: Language-external Factorsmentioning
confidence: 99%
“…The literature on language development of bilingual children has consistently shown that one of the most important languageexternal factors predicting bilingual language acquisition is the amount of exposure (Gathercole and Thomas, 2005;Guiberson et al, 2006;Armon-Lotem et al, 2011;Blom and Vasić, 2011;Chondrogianni and Marinis, 2011;Paradis, 2011;Anderson, 2012;Unsworth, 2013Unsworth, , 2015Paradis and Jia, 2016, among many others). In a setting with one dominant societal language and a minority language, a child's input is typically divided between the two languages and comes from two main sources: home and school.…”
Section: Language-external Factorsmentioning
confidence: 99%
“…For example, children with access to bilingual or L2 schooling or substantial and consistent L2 input demonstrated more skills in that language than did children who did not receive enriched L2 input. The relationship between language input and variability in bilingual proficiency has also been documented in TD bilingual children (Guiberson, Barrett, Jancosek, & Yoshinaga-Itano, 2006;Paradis et al, 2011;Silva-Corvalan, 1991;Valdes & Figueroa, 1994). This variability should be expected because bilingualism is a continuum with a wide range of language proficiencies that are dynamic and that change over time (Kayser & Guiberson, 2008).…”
Section: Bilingual Development In Populations With Language Disordersmentioning
confidence: 87%
“…Accessibility to service questions were included in order to gather information about the importance of the accessibility and cost of services in relation to communication mode decisions. Also, several items from a Spanish parent survey of language development were used in order to gather detailed information about child and family bilingual status and parental beliefs about bilingualism (Guiberson et al, 2006;Guiberson & Rodriguez, 2010).…”
Section: Methods Surveymentioning
confidence: 99%
“…The author found that patterns of language use among immigrant children changed significantly at home as they learned English: With an increase in English language use children used less of native language. This pattern emerged faster with young children (Guiberson et al, 2006).…”
mentioning
confidence: 84%